STRATEGI BANDUNG SEBAGAI KOTA KREATIF DALAM UNESCO CREATIVE CITIES NETWORK (UCCN) - Sari, Mira Nofrika; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research discusses the strategy of the Bandung City Government in making Bandung City as a UNESCO Creative City. Bandung is one of three cities in Indonesia that was included in the UNESCO Creative Cities Network (UCCN) in 2015. Currently, the city has become a joint discussion in international meetings. The important role of cities in promoting community-focused sustainable development and respecting for human rights is specifically recognized in the 2030 Agenda. This qualitative study questions the strategy used by the Regional Government (Pemda) in following the international development agenda